Factors Related to Unsafe Actions in Maintenance Workers at PT Besmindo Materi Sewatama Duri – Riau - Fitria, Friska Eka; Larasati, Adisti Qamahadlina (RADINKA JOURNAL OF HEALTH SCIENCE, 2024)
Based on an preliminary survey conducted at PT Besmindo Materi Sewatama, it was found that more than half of the incidents of work accidents were caused by unsafe actions of workers in the maintenance section. The purpose of the study was to determine the factors associated with unsafe acts in maintenance workers of PT Besmindo Materi Sewatama in 2024. This research was conducted at PT Besmindo Materi Sewatama in the maintenance department from April to July 2024. This research is a quantitative study with a cross-sectional design. The research sample amounted to 30 people. The sampling technique used was total sampling. The results showed that there was a relationship between knowledge and unsafe acts (P = 0.000) and there was no relationship between work supervision and unsafe acts (p = 0.123). It is recommended for supervisors to make standard operating procedures to work safely for maintenance workers.